Eosinophilic gastroenteritis in pregnancy: A review of the literature. (May 2020) - Amadori, Roberta; Stampini, Viviana; Rapetti, Rachele; Pirisi, Mario; Vigone, Alessandro; Surico, Daniela
Abstract: Eosinophilic gastroenteritis (EGE) is an uncommon and heterogeneous disease characterized by eosinophilic infiltration of the gastrointestinal tract. There are very few reports in literature describing pregnancies in EGE patients, and no review has ever been published. We found a total of 12 cases including one that occurred in our clinic. In 5 out of 12 cases, EGE was diagnosed after delivery and pregnancies are described as uneventful. Of the 5 patients who already had a diagnosis of EGE before pregnancy, only one registered an improvement of symptoms during gestation, while the rest had no significant changes, and their pregnancies needed to be monitored as high risk. Regarding pregnancy complications, only two patients had a pre-term delivery. Both patients had not only EGE, but a remarkable obstetrical history, that could slightly complicate the interpretation of the events that occurred in their pregnancies. More studies are necessary to demonstrate if EGE is connected with pre-term onset of labor. It's not easy to define the reasons of some patient's pre term labor, and we could suppose that a combination of different mechanisms leads to this condition of breakdown of maternal-fetal tolerance. Nevertheless, we know that spontaneous preterm labor is a syndrome attributable to multiple pathologic processes and most of them are yet to be understood. However, we cannot exclude that EGE is related to late preterm delivery. We hope that this review will provide some measures of guidance to those clinicians who must satisfy the questions of young female patients diagnosed with EGE and wishing for a pregnancy.